GraphoGame: between the gamification of childhood and the demoralization of basic education (Simbiótica. Revista Eletrônica, 2025)
To solve the educational gap caused by the coronavirus pandemic, then President Jair Bolsonaro suggested, in a debate held in October 2022, the use of the GraphoGame application, enabling educational and technological debates about games as a teaching practice. Therefore, the purpose of this article is to discuss the implementation of games in the educational processes of children and young people to understand the contribution to literacy and literacies. In this way, based on the theoretical framework of multiliteracies, exploratory research was carried out in the GraphoGame app. From this, it was noticed that it is necessary to think about literacy policies that prioritize social contexts and experimentation with various language modes beyond the simple insertion of games in educational contexts.
Keywords: Ludoliteracies; Graphogame; Gamification; Games and Education